Green finance and sustainability : environmentally-aware business models and technologies - Luo, Zongwei, 1971- (Hershey, PA : Business Science Reference, 2011)
'This book is devoted to examining a range of issues concerning green finance and sustainability covering sections on emerging environmentally aware business models, regulation and standard development, green ICT for sustainability, green finance and the carbon market, green manufacturing, logistics and SCM, and regional low carbon development'--Provided by publisher.
Includes bibliographical references (p. 569-612) and index.
Keywords: Industrial management -- Environmental aspects; Sustainable development -- Environmental aspects; Industries -- Environmental aspects; Finance -- Environmental aspects